2004
DOI: 10.1037/0278-6133.23.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in Outcomes of Heart Surgery: The Impact of Religious Involvement and Depressive Symptoms.

Abstract: This article reports a prospective study of religiousness and recovery from heart surgery. Religiousness and other psychosocial factors were assessed in 142 patients about a week prior to surgery. Those with stronger religious beliefs subsequently had fewer complications and shorter hospital stays, the former effect mediating the latter. Attendance at religious services was unrelated to complications but predicted longer hospitalizations. Prayer was not related to recovery. Depressive symptoms were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
111
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 53 publications
(88 reference statements)
9
111
1
4
Order By: Relevance
“…Intrasurgical factors and complications have added impact (Contrada et al, 2004). Limited work on psychosocial factors points to possible effects of depression, religion (Contrada et al, 2004), subjective health indicators (Halpin & Barnett, 2005;G. Johnston, Goss, Malmgren, & Spertus, 2004), and social isolation (G. Johnston et al, 2004).…”
mentioning
confidence: 99%
“…Intrasurgical factors and complications have added impact (Contrada et al, 2004). Limited work on psychosocial factors points to possible effects of depression, religion (Contrada et al, 2004), subjective health indicators (Halpin & Barnett, 2005;G. Johnston, Goss, Malmgren, & Spertus, 2004), and social isolation (G. Johnston et al, 2004).…”
mentioning
confidence: 99%
“…Indeed even navigating the system prior to the point of surgery takes a significant psychological toll on the patient [22,23]. However, some specific psychosocial dimensions linked with surgery were also identified.…”
Section: Psychosocial Factors and Surgerymentioning
confidence: 99%
“…Specifically, psychosocial wellbeing, mood state and related factors have a major influence over hospitalisation, healing and surgical outcomes [14,24]. Pre surgery fear and anxiety have also been linked with post-operative depression, pain and poorer recovery [14,22].…”
Section: Psychosocial Factors and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Contrada et al (2004), it is shown that the statistical issues he raised, and his preferred interpretation of the findings, were adequately addressed in the original article. It is argued that methodological limitations also were fully characterized and do not differ in kind from those of biomedical studies.…”
mentioning
confidence: 99%